MORPHOLOGICAL ERRORS IN ARABIC WRITING AT DAARUL KHAIR ISLAMIC SCHOOL: KESALAHAN MORFOLOGIS INSYA SISWA DI PONDOK PESANTREN DAARUL KHAIR - Nita Zakiah; Puji Rahayu (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
This study examines morphological error analysis (ṣarf) as an effort to minimize errors in Arabic language learning. The research employed a qualitative descriptive approach with a case study design and was conducted among second-grade students at Daarul Khair Islamic Boarding School, Kotabumi. The data were collected from students’ insya (Arabic written compositions) through written tests and document analysis. The study aims to identify common morphological errors made by students in learning Arabic and to propose instructional strategies to address these errors. The findings reveal that the morphological errors predominantly occur in the use of taṣrīf lughawī (verb conjugation based on pronouns) and taṣrīf iṣṭilāḥī (derivational and functional word forms). The causes of these errors include interlingual factors arising from differences between the grammatical systems of the students’ first language (Indonesian) and Arabic as the target language, intralingual factors related to the complexity of Arabic morphological rules, and performance factors such as educational background, psychological conditions, and the learning environment. These findings highlight the importance of focused morphological instruction and systematic practice in improving students’ Arabic writing skills.